1999
DOI: 10.1074/jbc.274.46.32565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Central Phosphorylation Site in p21-activated Kinase Regulating Autoinhibition and Kinase Activity

Abstract: p21-activated kinases (Pak)/Ste20 kinases are regulated in vitro and in vivo by the small GTP-binding proteins Rac and Cdc42 and lipids, such as sphingosine, which stimulate autophosphorylation and phosphorylation of exogenous substrates. The mechanism of Pak activation by these agents remains unclear. We investigated Pak kinase activation in more detail to gain insight into the interplay between the GTPase/sphingosine binding, an intramolecular inhibitory interaction, and autophosphorylation. We present bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
221
4
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 226 publications
(233 citation statements)
references
References 21 publications
7
221
4
1
Order By: Relevance
“…This highly conserved site can be found in the activation loop of PKAc subunit as well (Thr197). In both cases, autophosphorylation has been confirmed upon kinase activation (42,43). In Fig.…”
Section: Pka Rii Subunits Form Protein Complexes With Rac1 In Vitro Amentioning
confidence: 77%
“…This highly conserved site can be found in the activation loop of PKAc subunit as well (Thr197). In both cases, autophosphorylation has been confirmed upon kinase activation (42,43). In Fig.…”
Section: Pka Rii Subunits Form Protein Complexes With Rac1 In Vitro Amentioning
confidence: 77%
“…The pellet was directly dissolved in a small volume of SDS-PAGE sample buffer. In vitro kinase assays with immunoprecipitated Pak1 were as described (29). The kinase inhibitors were from LC Laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Rac1(T17N) were a kind gift from Klaus Hahn (The Scripps Research Institute). Full-length GST-Pak1 and GST-PBD/ID(H83L) were expressed and purified by glutathione affinity chromatography as described (28,29). Plasmids containing wild-type and mutant Op18, samples of untagged Op18 and related proteins, and anti-Op18 antibodies were generous gifts of Martin Gullberg (University of Umeå, Umeå, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active Rac GTP precipitated by PAK-PBD was separated on SDS-PAGE, transferred to nitrocellulose membrane, and blotted for pan-Rac, followed by ECL detection. Left lanes, the total signal detected using cytosol preloaded with Chemokine-induced PI3K␥-Rac-Pak Signaling 43276 loop of the kinase domain and is known to be required for activation (41)(42)(43). The phospho-PAK Thr antibody demonstrated that RANTES stimulation of macrophages for 10 and 30 s triggered phosphorylation of PAK2 Thr-402 , but less so in PI3K␥Ϫ/Ϫ BMDM (Fig.…”
Section: Rantes-induced Rac Activationmentioning
confidence: 99%